2013
DOI: 10.1002/ijc.28553
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of cytoreductive nephrectomy and patient survival in the targeted therapy era

Abstract: We sought to analyze utilization and survival outcomes of cytoreductive nephrectomy in patients with metastatic renal cell carcinoma (RCC) before and after introduction of targeted therapy. We identified patients with metastatic RCC between 1993 and 2010 in the SEER registry and examined temporal trends in utilization. We performed a joinpoint regression to determine when changes in utilization of cytoreductive nephrectomy occurred. We fitted multivariable proportional hazard models in full and propensity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
80
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 19 publications
7
80
1
7
Order By: Relevance
“…Though the rate of CRN improved after 2001 perhaps with the results of the EORTC and SWOG trials [10,11], it appears that there was a steady decrease in its use which peaked at 39% in 2004 and has decreased every year by 0.6% since then [19]. Tsao et al also showed a similar pattern in their study in the targeted therapy era, but it is difficult to infer that this was a global phenomenon as both these studies were based on the Surveillance, Epidemiology, and End Results (SEER) data analysis from the USA [20].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Though the rate of CRN improved after 2001 perhaps with the results of the EORTC and SWOG trials [10,11], it appears that there was a steady decrease in its use which peaked at 39% in 2004 and has decreased every year by 0.6% since then [19]. Tsao et al also showed a similar pattern in their study in the targeted therapy era, but it is difficult to infer that this was a global phenomenon as both these studies were based on the Surveillance, Epidemiology, and End Results (SEER) data analysis from the USA [20].…”
Section: Discussionmentioning
confidence: 92%
“…A large study using the SEER database examined CRN and survival in the era of immunotherapy as well as TT and found an overall survival of 19 months for TT with CRN versus only 4 months of TT [19]. This study also inferred that the median OS amongst the patients receiving CRN improved from 13 to 19 months between the era of immunotherapy (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)) and the era of targeted therapy (2005)(2006)(2007)(2008)(2009)(2010) and there was no significant difference in OS in these two eras in patients who did not undergo CRN.…”
Section: Discussionmentioning
confidence: 99%
“…Появление таргетных препаратов, ингибиру-ющих сосудистый эндотелиальный фактор роста (VEGF) и мишень рапамицина млекопитающих (mTOR), позволило существенно улучшить прогноз и принципиально изменить стандарты лекарственно-го лечения больных распространенным раком почки [5]. При этом необходимость выполнения циторедук-тивных вмешательств пациентам, являющимся кан-дидатами для таргетной терапии, в рандомизирован-ных исследованиях не доказана [6].…”
unclassified
“…Пере-рыв и отмена лечения из-за тяжелых нежелательных явлений чаще также требовались неоперированным пациентам (20,0 %) по сравнению с больными, кото-рым была выполнена паллиативная нефрэктомия (4,2 %), однако разница результатов между группами не достигла статистической значимости. В немногочи-сленных ретроспективных исследованиях, изучавших результаты таргетной терапии с паллиативной нефрэк-томией и без нее, токсичность и безопасность лекарст-венного лечения в группах не сравнивались [6,[17][18][19][20].…”
unclassified
See 1 more Smart Citation